TEKST MULTIMODALNY W GLOTTODYDAKTYCE - Makowska, Magdalena (Neofilolog, 2018)
Multimodality as a linguistic universal plays a substantial role not only in the process of communication but also e.g. in philological instruction. It is used both in handbooks as well as all kinds of other didactic materials available in the printed version and the electronic one alike. However, in order for it to constitute practical assistance for a student and real help for the teacher, they must have the so-called multimodal competence at their disposal, which will both at the stage of text production as well as in the phase of its reception enable them to fully use the potential inherent in multimodality. The aim of the article is to show in what way multimodality made use of in foreign language handbooks changes philological education, making it more effective and attractive for all the sides engaged in this process.